Randomized, placebo-controlled trial of incobotulinumtoxina for upper-limb post-stroke spasticity - Elovic, Elie Paul; Munin, Michael C; Kaňovský, Petr; Hanschmann, Angelika; Hiersemenzel, Reinhard; Marciniak, Christina (Muscle & nerve, 2016)
INTRODUCTION: Efficacy and safety of incobotulinumtoxinA in post-stroke upper-limb spasticity were studied. METHODS: Subjects randomized 2:1 to incobotulinumtoxinA (fixed dose 400 U) or placebo, with fixed doses for the primary target clinical pattern (PTCP; flexed elbow, 200 U; flexed wrist, 150 U; clenched fist, 100 U). Doses for non-primary patterns were flexible within predefined ranges. RESULTS: At week 4, incobotulinumtoxinA led to larger improvements in PTCP Ashworth scale (AS) scores than placebo [least-squares mean change ± standard error: -0.9 ± 0.06 (n = 171) vs. -0.5 ± 0.08 (n = 88); P < 0.001], and more subjects were PTCP AS responders (≥1-point improvement) with incobotulinumtoxinA (69.6%) than with placebo (37.5%; P < 0.001). Investigator's Global Impression of Change confirmed superiority of incobotulinumtoxinA vs. placebo (P = 0.003). IncobotulinumtoxinA was associated with functional improvements, as demonstrated in responder rates for Disability Assessment Scale principal target at week 4 (P = 0.007). Adverse events were mainly mild/moderate, and were reported by 22.4% (incobotulinumtoxinA) and 16.8% (placebo) of subjects. CONCLUSIONS: IncobotulinumtoxinA significantly improved upper-limb spasticity and associated disability, and was well-tolerated.
Keywords: muscle spasticity; botulotoxiny typu A; Neuromuscular Agents; Humans; lidé středního věku; Stroke; Double-Blind Method; botulinum toxins, type A; Xeomin; Female; Aged; analýza rozptylu; dospělí; mladý dospělý; Botulinum Toxins, Type A; Analysis of Variance; senioři; dvojitá slepá metoda; lidé; stroke; horní končetina; cévní mozková příhoda; Adult; ženské pohlaví; stupeň závažnosti nemoci; Male; Middle Aged; Muscle Spasticity; Retrospective Studies; Adolescent; Upper Extremity; svalová spasticita; Aged, 80 and over; Severity of Illness Index; Young Adult; senioři nad 80 let; retrospektivní studie; mužské pohlaví; nervosvalové látky; incobotulinumtoxinA; mladiství